(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Due to the increased demand for technical specialists in digitalized infrastructure in all spheres, universities are facing the requirement to enlarge student abilities with English academic pieces of knowledge based on their programs. By gaining English academic terminology in their sphere, the graduates enlarge their opportunities to be attracted by prestigious employers. This paper aims to present the effective integrated teaching approaches that have been analyzed by ESP practitioners and suggested as the key solution to deal with content-based teaching.